Effects of reduced exposure to societal language on vocabulary and morphological knowledge of bilingual children - Anat Prior; Gal Pedael (Language Development Research, 2025)
Children’s vocabulary and morphological knowledge both arise from exposure to their surrounding language, albeit through different learning mechanisms. Vocabulary is driven mostly by exposure to specific words, namely token exposure, whereas knowledge of morphological regularities also arises from cumulative exposure to language patterns, namely type exposure. Here we examine the impact of the reduced exposure of bilingual children to the societal language, Hebrew, on their vocabulary and morphological knowledge. The study included 148 preschool children (half bilingual) who performed a productive vocabulary task, two inflection and two derivation tasks. One of the inflectional tasks used pseudo-words in order to examine abstract morphological knowledge while neutralizing lexical knowledge. Overall, bilingual children showed lower performance than monolingual peers across both vocabulary and morphological tasks. Importantly, error analyses, tapping into participants’ ability to utilize morphological knowledge in the absence of lexical representations, revealed equivalent performance of bilingual and monolingual children in inflection, and small differences in derivation. Methodologically, these results highlight the importance of de-coupling lexical and morphological knowledge, especially when studying bilingual individuals. Theoretically, the current findings suggest that the acquisition of morphological regularities, driven mostly by type exposure, is more resilient than the acquisition of lexical knowledge, driven by token exposure, in the face of reduced exposure associated with bilingualism.